103 Virtual multiple sclerosis (MS) clinics during a global pandemic: the patients' perspective. Issue 6 (27th May 2022) - Ramsay, Stephen; Turley, Niamh; Magill, Fiona; Goldsmith, Grainne; McKee, Jon; Kennedy, Fiona; Droogan, Aidan; Hughes, Stella; McDonnell, Gavin
Abstract : Background: Within our service, all scheduled face-to-face neurology clinics were cancelled from March 2020 due to Covid-19. Telephone reviews were initiated to provide continuity of MS care. Objective: To assess patient satisfaction with MS telephone clinics during the pandemic and opinion regarding potential future use. Design/Methods : Anonymised questionnaires were posted to 635 patients receiving MS specialist medical telephone review, March to July 2020. Results: 279 (44%) patient questionnaires were returned, mean age 49 years, 72% female, 87% having an EDSS <7.0. On a rating scale, (0–10, 10 = completely satisfied), 95% of patients reported a satisfaction score ≥7. For 99% of patients, clinical interaction was caring/sensitive by telephone. Satisfaction was high with: call duration (96%), opportunity to ask questions (99%) and understanding advice given (98%). During the pandemic, 87% of patients preferred the virtual appointment. Of all patients, 45% expressed preference for telephone review moving forward, rising to 55% among both wheelchair-using patients and those living >50 miles from clinic. Many felt that video call would further improve virtual review (54%). Conclusions: During the COVID-19 pandemic, satisfaction is high with MS review by telephone. A signifi- cant body of patient opinion supports telephone clinics beyond Covid-19. This is influenced by EDSS and distance from clinic. sramsay03@qub.ac.uk|ABN Bursary